The success of using 2% lidocaine in pain removal during extraction of mandibular premolars: a prospective clinical study - Firas A. Jamil; Huda Moutaz Asmael; Mohammed Yahya Al-Jarsha (BMC, 2020)
Abstract Background The purpose of this study was to evaluate the anesthetic effectiveness of a buccal infiltration technique combined with local massage (using 2% lidocaine) in the extraction of mandibular premolars to be utilized as an alternative to the conventional inferior alveolar nerve block. Methods Patients eligible included any subject with a clinical indication for tooth extraction of the mandibular 1st or 2nd premolars. All patients were anesthetized buccally by local infiltration technique followed by an external pressure applied for 1 min directly over the injection area. In each case, another local injection was given lingually. All operations were started at approximately 5 min after the buccal injection. The collected data included age, gender, pain perception and its intensity during treatment at three checkpoints, apical tenderness, and the type of extraction. Any associated complications or difficulties were also recorded. Then the results were analyzed and interpreted using appropriate statistical tests. The significance level was set at P ≤ 0.05. Results A total of 247 cases (1st premolar, n = 119; 2nd premolar, n = 128), predominantly male, were included. In 95% of study sample, the patients were satisfied with the dental extraction without any pain. However, in 5% of cases, pain was reported at the stage of tooth removal. Apical tenderness was found to be present in 11% of the total cases. Three teeth required surgical removal. Upon analysis, no significant differences in the success rates were detected between the 2 premolar groups or amongst the various age groups. Minor and transient side effects were reported in this study. Conclusion The technique is simple and effective as well. It might be considered as an alternative anesthetic injection to the inferior alveolar nerve block for dental extraction of the mandibular premolars.